GLA/DRST real-world outcome analysis of CAR T-cell therapies for large B-cell lymphoma in Germany - Bethge, Wolfgang Andreas; Martus, Peter; Schmitt, Michael; Holtick, Udo; Subklewe, Marion; von Tresckow, Bastian; Ayuk, Francis; Wagner-Drouet, Eva Marie; Wulf, Gerald G.; Marks, Reinhard; Penack, Olaf; Schnetzke, Ulf; et al. (Blood, 2022)
CD19-directed chimeric antigen receptor (CAR) T cells have evolved as a new standard-of-care (SOC) treatment in patients with relapsed/refractory (r/r) large B-cell lymphoma (LBCL). Here, we report the first German real-world data on SOC CAR T-cell therapies with the aim to explore risk factors associated with outcomes. ...